The Part and Parcel of Doctoral Education: A Gap Analysis between the Importance and Satisfaction of the Experience - Gregory Siy Ching; Yueh-Luen Hu; Amy Roberts (MDPI AG, 2021)
The doctoral student experience is complex and multifaceted, and although it is increasingly examined in higher education research, there is still much to explore and understand about the topic. Despite expanding discourse, few investigations have been conducted in the East Asian context with multiple universities and fields of study. The present paper aimed to overcome these limitations with research conducted in two Taiwan universities with 94 doctoral student subjects. The study was designed as a quantitative cross-sectional survey using gap analysis. Results showed that within three dimensions (experience with mentors, peers, and curricular engagements) nine distinct variables were validated. The importance of peer interaction and support from mentors were noted as key components for a successful, enjoyable doctoral experience within the Taiwan context.